2012
DOI: 10.1111/jpy.12017
|View full text |Cite
|
Sign up to set email alerts
|

Algal Parasite Herpodiscus durvillaeae (Phaeophyceae: Sphacelariales) Inferred to have Traversed the Pacific Ocean with its Buoyant Host

Abstract: The parasitic phaeophycean endophyte Herpodiscus durvillaeae (Lindauer) G. R. South has previously only been recorded from New Zealand, in association with a single host species, Durvillaea antarctica (Chamisso) Hariot (southern bull-kelp). Here we use DNA sequence data from plastid and nuclear markers (chloroplast rbcL, ribosomal LSU, and a nuclear pseudogene copy of COI) to test for the presence of H. durvillaeae beyond the New Zealand region, and on host species other than D. antarctica. Analyses of samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Further sampling could help to clarify the direction of travel. Our finding supports previous inferences of long-distance dispersal of marine pathogens via rafting with buoyant macroalgae (Fraser and Waters 2013;Blake et al 2017). Blake et al (2017) found M. ectocarpii in Australia on bull kelp taxa D. potatorum and D. amatheiae, so we might have expected to find M. ectocarpii in New Zealand (geographically relatively close to Australia), but these solid-bladed Durvillaea species are non-buoyant and thus have limited dispersal opportunities (Fraser et al 2020;Hay 2020).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Further sampling could help to clarify the direction of travel. Our finding supports previous inferences of long-distance dispersal of marine pathogens via rafting with buoyant macroalgae (Fraser and Waters 2013;Blake et al 2017). Blake et al (2017) found M. ectocarpii in Australia on bull kelp taxa D. potatorum and D. amatheiae, so we might have expected to find M. ectocarpii in New Zealand (geographically relatively close to Australia), but these solid-bladed Durvillaea species are non-buoyant and thus have limited dispersal opportunities (Fraser et al 2020;Hay 2020).…”
Section: Resultssupporting
confidence: 89%
“…This trait has promoted long-distance dispersal of Durvillaea species such as D. antarctica, which has been found washed up on coasts thousands-and even tens of thousands-of kilometres away from known source populations (Moore and Cribb 1952;Fraser et al 2011Fraser et al , 2018Waters et al 2018). These buoyant species are an important mechanism for the dispersal of coastal taxa, as they can transport other organisms with them, such as invertebrates, other algal species, and marine parasites (Thiel and Gutow 2005a, b;Fraser and Waters 2013). Emerging data showing a wide distribution of Maullinia across the Southern Hemisphere suggest that Maullinia might also disperse with these buoyant hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic studies have become a common tool to identify new parasite species (Sekimoto et al 2009;Skovgaard & Salomonsen 2009), investigate their origin (Litaker et al 1999;Skovgaard et al 2007;Barkman et al 2008) and host switching (Fraser & Waters 2013;Pelser et al 2016). Molecular data are still rather limited for red algal parasites with only 27% of all red algal parasites having been sequenced (Chapter 2).…”
Section: Diversity and Evolution In Parasitesmentioning
confidence: 99%